Impact of gear rim narrowing angle on the temperature and sound pressure of Beveloid gear pair made of polymeric materials - Piotr Strojny (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2021)
The paper contains a description of the geometry of Beveloid gears. It describes the distribution of forces in a Beveloid gear with a straight tooth line and a helical tooth line. The paper presents research on the experimentally determined parameters of transmission operation, including the sound pressure level and the amount of heat emitted during operation. The design and construction of the test stand were presented. The research methodology was described. Operational tests are carried out on household appliances with Beveloid gears: Grinder and Jam mixer. Thanks to an appropriately selected narrowing angle, estimated values of service life extension of the above-mentioned transmissions are given.